Unravelling the Worldwide Pollution Haven Effect - Jean-Marie Grether; Nicole A. Mathys; Jaime de Melo (Fondation pour les études et recherches sur le développement international (FERDI), 2012)
This paper tackles the "pollution haven" argument by estimating the pollution content of imports (PCI). The PCI is then decomposed into three components:(i) a "deep" component (i.e. traditional variables unrelated to the environmental debate); (ii) a factor endowment component and (iii) a "pollution haven" component reflecting the impact of differences in environmental policies. Theestimation is carried out for 1987 for an extensive data set covering 10 pollutants, 48 countries and 79 ISIC 4-digit sectors.
Keywords: F18; Q56; 330